2018
DOI: 10.4018/ijkm.2018010104
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing Barriers in Vietnamese Higher Education Institutions (HEIS)

Abstract: This article explores the barriers for sharing knowledge effectiveness in Vietnamese higher education institutions (HEIs). Data were analyzed and triangulated from interviews, and focus groups from different universities and from government and university websites. Three significant factors were identified: bureaucratic management causing a lack of autonomy in decision-making, poor knowledge management systems, and weak individual absorptive capacity. The results demonstrate these three factors as a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 64 publications
0
9
0
1
Order By: Relevance
“…A számos előny mellett egyéni, szervezeti, technológiai akadályok (Riege 2005), a tudásmenedzsment elégtelen minősége (Van Ta-Zyngier 2018), illetve egyéb akadályok is gátolhatják a tudásmegosztást és a tudásátadást.…”
Section: Tudásmenedzsment-tudásátadásunclassified
“…A számos előny mellett egyéni, szervezeti, technológiai akadályok (Riege 2005), a tudásmenedzsment elégtelen minősége (Van Ta-Zyngier 2018), illetve egyéb akadályok is gátolhatják a tudásmegosztást és a tudásátadást.…”
Section: Tudásmenedzsment-tudásátadásunclassified
“…Vietnamese higher education is heavily influenced by external systems, especially China and the West, in terms of organizing structures and policies, curriculum content, intellectual influences, teaching methodology, and quality assurance, for example (Le, 2014;Nguyen & Hamid, 2015;Tran & Marginson, 2018;Tran et al, 2017Tran et al, , 2020. Studies have identified a range of reasons for weak research capacity (Pho & Tran, 2016;Ta & Zyngier, 2018), but underneath individual and institutional difficulties lies a lack of confidence in building an independent research system and foregrounding a distinctive voice. Our study aims to give voice to the practitioners of service-learning in Viet Nam as the foundation for further research.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous studies find that some of the value derived from investments in BDA information systems has yielded mixed results [51,53]; in fact, while some studies have argued that BDA and KM do not necessarily lead to better organizational performance or that KM has a partial mediating effect between BDA and organizational performance [39], other studies have found positive associations between the two [53]. Previous research established that KM processes significantly influence organizational performance in HEIs [101][102][103]; some authors even highlight their contribution in terms of measures such as innovativeness or new product introduction [104].…”
Section: Relationship Between Km Processes and Bda And Its Mediating Role With Organizational Performancementioning
confidence: 99%